Influence of Procurement Best Practices in Optimizing Procurement Performance among Parastatals in Kenya - Munene, Marion Wanjiku; Achuora, John (My University, 2018)
The main objective of the study was to examine the influence of procurement best practices in optimizing procurement performance among parastatals in Kenya. To gather data, structured questionnaire will be used to collect data from a sample of 127 respondents, who were selected using simple random sampling, from the four strata. The response rate of the study was 82%. The findings of the study indicated that reverse logistics management, business process outsourcing, strategic partnerships and organizational benchmarking have a positive relationship with procurement performance among parastatals in Kenya. Finally, the study recommended that public institutions should embrace procurement best practices so as to improve performance and further researches should to be carried out in other public institutions to find out if the same results can be obtained
Keywords: Reverse logistics management; Business process outsourcing; Strategic partnerships; Organizational benchmarking